2016
DOI: 10.15560/12.1.1839
|View full text |Cite
|
Sign up to set email alerts
|

Species richness and conservation status of medium and large terrestrial mammals from four Sky Islands in Sonora, northwestern Mexico

Abstract: Abstract:We present the first systematic checklist of medium and large terrestrial mammals on four mountain ranges known as Sky Islands, in northeastern Sonora, Mexico. We used camera traps for recording mammals, with which we documented 25 wild species. Two of the native species are in the IUCN Red List and four are threatened at the national level. We did not document seven wild species with potential distribution at study sites, probably due to limited availability of habitat and/ or local extirpation of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Some comprehensive inventories have been conducted in some CONABIO terrestrial priority areas (Arriaga et al, 2000), Alta Tarahumara-Barrancas, Chihuahua (RTP 30; López-González & García-Mendoza, 2006), San Juan de Camarones, Durango (RTP-23;Torres-Morales et al, 2010), San Pedro-Mezquital river basin, Durango and Nayarit (RTP 57;López-González et al, 2014a), and Jesús María River basin, Nayarit (RTP 59; García-Mendoza et al, 2021;López-González et al, 2022). Other inventories have focused on protected areas like la Michilía, Durango (Álvarez & Polaco, 1984); Área de Protección de Flora y Fauna Bavispe, Sonora (Coronel-Arellano et al, 2016;; and Cerro Mohinora, Chihuahua (Webb & Baker, 1984).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some comprehensive inventories have been conducted in some CONABIO terrestrial priority areas (Arriaga et al, 2000), Alta Tarahumara-Barrancas, Chihuahua (RTP 30; López-González & García-Mendoza, 2006), San Juan de Camarones, Durango (RTP-23;Torres-Morales et al, 2010), San Pedro-Mezquital river basin, Durango and Nayarit (RTP 57;López-González et al, 2014a), and Jesús María River basin, Nayarit (RTP 59; García-Mendoza et al, 2021;López-González et al, 2022). Other inventories have focused on protected areas like la Michilía, Durango (Álvarez & Polaco, 1984); Área de Protección de Flora y Fauna Bavispe, Sonora (Coronel-Arellano et al, 2016;; and Cerro Mohinora, Chihuahua (Webb & Baker, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, between 2000 and 2020, three new species have been discovered using morphological or molecular means (Peromyscus schmidlyi Bradley, Carroll, Muñiz-Martínez, Hamilton & Kilpatrick, 2004; Peromyscus carletoni Bradley, Ordóñez-Garza, Sotero-Caio, Huynh, Kilpatrick, Iñiguez-Dávalos & Schmidly, 2014; and Thomomys nayarensis Mathis, M. S. Hafner, D. J. Hafner, & Demastes, 2013b), and some populations formerly named Thomomys umbrinus (Richardson, 1829), are now recognized as a different taxon (T. sheldoni Bailey, 1915;Mathis et al, 2013a), which suggests that as species groups are studied using integrative taxonomy approaches, more species that so far remain cryptic will be discovered, either in the field or in collections. In addition, further research is being conducted using camera-traps in the northwestern edge of the SMO that is documenting medium-sized and large mammals in selected protected areas (Espinosa-Flores et al, 2012;Coronel-Arellano et al, 2016;Gallo-Reynoso et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We include Sciurus arizonensis because of its IUCN Data Deficient status and note that the species is listed as Threatened in México (Coronel-Arellano et al 2016). Bailey (1931 reported that the Arizona gray squirrel is common along the San Francisco River, and Findley et al (1975) recounted that it is "limited to the deciduous riparian forest of the San Francisco drainage in Catron Co. " However, as Hayward and Hunt (1972) observed, Arizona gray squirrels have been extending their range up the Gila and San Francisco drainages and east towards the Rio Grande.…”
Section: Discussionmentioning
confidence: 99%